Effect of Fluorine in the Synergism Co-Mo Via Hydrogen Spillover on the Hydrodesulphurization of Refractory Molecules - Gil-Llambias, F (Sociedad Chilena de Quimica, 2013)
The influence of fluorine concentration on the synergism between Co/?-Al2O3 and Mo/?-Al2O3 stacked beds separated by 3-mm of ?-Al2O3Fx (x = 0 - 2.5%), in the hydrodesulphurization of refractory molecules contained in gasoil, under operating conditions similar to those of industry, was studied. The results shown, that the synergism increases with F content, reaching a maximum at 0.8% of fluorine, which it is related to changes in zero point of charge (ZPC) and acid strength, due to the incorporation of fluorine. The conversion of most refractory molecule reported is favoured by fluorine.